HDI XMAS July 15, 2019. Melvin Harnum Photos. - Barrett, Terra (1983)
A photo of people gathered and day drinking in Heart's Delight before Christmas Carolling on Christmas Eve. Seated Eric Parsons, Robert Harnum, Melvin Harnum, and Glen Walsh.